Structural Behaviour of Self Consolidating Steel Fiber Reinforced Concrete Beams - Cohen, Michael I. (Université d'Ottawa / University of Ottawa, 2012)
When subjected to a combination of moment and shear force, a reinforced concrete (RC) beam with either little or no transverse reinforcement can fail in shear before reaching its full flexural strength. This type of failure is sudden in nature and usually disastrous because it does not give sufficient warning prior to collapse. To prevent this type of shear failure, reinforced concrete beams are traditionally reinforced with stirrups. However, the use of stirrups is not always cost effective since it increases labor costs, and can make casting concrete difficult in situations where closely-spaced stirrups are required. The use of steel fiber reinforced concrete (SFRC) could be considered as a potential alternative to the use of traditional shear reinforcement. Concrete is very weak and brittle in tension, SFRC transforms this behaviour and improves the diagonal tension capacity of concrete and thus can result in significant enhancements in shear capacity. However, one of the drawbacks associated with SFRC is that the addition of fibers to a regular concrete mix can cause problems in workability. The use of self-consolidating concrete (SCC) is an innovative solution to this problem and can result in improved workability when fibers are added to the mix. The thesis presents the experimental results from tests on twelve slender self-consolidating fiber reinforced concrete (SCFRC) beams tested under four-point loading. The results demonstrate the combined use of SCC and steel fibers can improve the shear resistance of reinforced concrete beams, enhance crack control and can promote flexural ductility. Despite extensive research, there is a lack of accurate and reliable design guidelines for the use of SFRC in beams. This study presents a rational model which can accurately predict the shear resistance of steel fiber reinforced concrete beams. The thesis also proposes a safe and reliable equation which can be used for the shear design of SFRC beams.
Keywords: Steel Fiber; Self Consolidating Concrete; Mustafa Mohammed-Saeed; SFRC; SCFRC; Steel Fiber Reinforced Concrete Beams; SCC; SFRC Beams; SCFRC Beams; Shear Behaviour of SFRC Beams; Slump Flow Test; Fiber Pullout Strength; Mohammed-Saeed; Mustafa; Michael; Cohen; Shear Behaviour of SCFRC Beams